Numerical study of the effects of lamp configuration and reactor wall roughness in an open channel water disinfection UV reactor. (July 2016) - Sultan, Tipu
Abstract: This article describes the assessment of a numerical procedure used to determine the UV lamp configuration and surface roughness effects on an open channel water disinfection UV reactor. The performance of the open channel water disinfection UV reactor was numerically analyzed on the basis of the performance indictor reduction equivalent dose (RED). The RED values were calculated as a function of the Reynolds number to monitor the performance. The flow through the open channel UV reactor was modelled using a k-ε model with scalable wall function, a discrete ordinate (DO) model for fluence rate calculation, a volume of fluid (VOF) model to locate the unknown free surface, a discrete phase model (DPM) to track the pathogen transport, and a modified law of the wall to incorporate the reactor wall roughness effects. The performance analysis was carried out using commercial CFD software (ANSYS Fluent 15.0). Four case studies were analyzed based on open channel UV reactor type (horizontal and vertical) and lamp configuration (parallel and staggered). The results show that lamp configuration can play an important role in the performance of an open channel water disinfection UV reactor. The effects of the reactor wall roughness were Reynolds number dependent. The proposed methodology is useful for performance optimization of an open channel water disinfection UV reactor. Graphical abstract: Highlights: The effects of horizontal and vertical lamp positioning on the performance of an open channel UV reactor were analyzed. The effects of parallel and staggered lamp positioning on the performance of an open channel UV reactor were analyzed. Vertical type with staggered lamp positioning results in a better performance. The effects of reactor's wall roughness on the performance of an open channel UV reactors were analyzed. The effects of roughness on RED were Reynolds number dependent.